Factors Influencing Nurses Performance in Implementing the Professional Nursing Practice Model - Yulia, Arini Dwi; Suroso, Jebul; Etlidawati, Etlidawati; Linggardini, Kris (Genius Journal, 2024)
Introduction: Nursing performance plays a pivotal role in determining the quality of healthcare services, especially in the application of professional nursing models. Several factors, both internal and external, influence nursing performance, including job satisfaction, work culture, workload, supervision, and experience. Understanding these relationships is essential for improving the quality of care in healthcare facilities, particularly hospitals. Objective: To analyze the relationship between various factors, including job satisfaction, work culture, workload, supervision, and experience, with nurses' performance in implementing the Professional Nursing Practice Model. Methods: This study employed a quantitative descriptive approach with a cross-sectional design. The sample consisted of 30 inpatient nurses selected through total sampling. Data were collected using structured questionnaires and analyzed using the chi-square test. Results: Most respondents were female, held a D3 education level, and had five years of work experience. The chi-square test revealed significant relationships between job satisfaction (p = 0.004), work culture (p = 0.002), workload (p = 0.004), supervision (p = 0.001), experience (p = 0.007), and the implementation of the Professional Nursing Practice Model. Conclusion: There is a significant relationship between job satisfaction, work culture, workload, supervision, experience, and the application of the Professional Nursing Practice Model, as evidenced by p-values less than 0.05. Improving these factors can enhance nurse performance and overall quality of care in hospitals.